(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
Introduction. In the world, practice of soil research there is ASTM Standard Test Method for Measurement of Soil Potential (Suction) Using Filter Paper D 5298-16. However, unfortunately, in Russia there are no defining documents related to negative pore pressure, or matrix suction, or SWCC, yet. Materials and methods. In this study, as a practical example of the effect of suction pressure on slope stability, the authors considered an object located in Zelenograd. Because of the experiment, SWCC was obtained and a geomechanical model was created. Results. Thus, for cover loams, the value of the initial suction pressure is 17 kPa. The value of matrix suction is 199 kPa. For fluvioglacial loams, the value of the initial suction pressure is 14 kPa. The value of matrix suction according to the graph is 207 kPa. Discussion and conclusion. Subsequently, calculations were performed in the Plaxis software without taking into account the suction pressure and with taking into account the suction pressure, while all other model parameters remained unchanged.